Pengaruh Penerapan Sistem E-Filling, Pengetahuan Perpajakan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak (Studi pada Wajib Pajak Orang Pribadi yang Melakukan Kegiatan Usaha Bebas Di Bintaro Trade Center) - Ahmad Burhan Zulhazmi; Febrian Kwarto (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
This study aims to determine and analyze the influence of the application of e-filing systems, tax knowledge, and tax awareness to tax compliance. This study uses primary data obtained from questionnaire data distributed to respondents who are required to tax individuals who carry out free business activities at the Bintaro Trade Center (BTC). The sampling technique uses purposive sampling. The analysis technique uses multiple linear regression analysis. The results of this study indicate that simultaneously, the variable implementation of e-filing systems, knowledge of taxation and awareness of taxpayers on tax rates. Application of e-filing system and awareness of taxpayers to mandatory obligations, while knowledge of taxation does not involve taxpayer obligations.